Effects of the COVID-19 Lockdown on Portuguese Children’s Motor Competence - Pombo, André (2022)
During long periods without school, children are more susceptible to unhealthy behaviors, such as an increase in sedentary behaviors, which has a negative impact on children’s motor competence (MC). The COVID-19 lockdown offered us a unique opportunity to test, in a quasi-experimental setting, the impact of lockdown movement restrictions on children’s MC. We assessed the motor competence of 114 children aged 6–9 years using the motor competence assessment. All children were tested before and after the COVID-19 lockdown. Chi-square and 2 × 2 ANOVA (sex by moment) were used to further analyze the data. Regardless of sex, motor performances in all tests (except for jumping sideways in boys) were lower when compared with performances before lockdown. There was a marked decreasing trend in children’s levels of MC, shifting from an upper to a lower quartile in different tests. The results after the lockdown were always significantly inferior to the results before lockdown in all motor tests (except jumping sideways), in the three components of MC, and in global MC. Children’s global MC score decreased by an average of 13 points in boys and 16 points in girls. The imposed movement restrictions had a negative effect on children’s motor competence development.